Weed Control and Corn Yield Following Preemergence and Sequential Applications of Mesotrione-based Premixtures - Patrick W. Geier; Sarah H. Lancaster (Kansas Agricultural Experiment Station Research Reports, 2025)
All herbicides evaluated provided good control of Palmer amaranth, kochia, and Russian thistle at Garden City and Palmer amaranth and common sunflower at Manhattan early in the season. Control of Russian thistle at Garden City, sunflower at Manhattan, and Palmer amaranth at both locations remained high with all treatments throughout the season. Trivolt at 20 oz/a controlled entireleaf morningglory 73% at Manhattan early in the season. Morningglory control was greater than 92% with all treatments except Storen at 2.4 qt/a plus atrazine or Acuron preemergence (PRE) later in the season. Minor (<10%) corn injury was observed at Manhattan, but grain yields did not differ by the end of the season. At Garden City, grain yields were highest when Acuron plus atrazine or Storen plus atrazine were applied PRE, and when split applications of Lumax EZ or Storen were applied PRE followed by postemergence (POST). Producers need to be aware that below-labeled rates of herbicides can increase the risk of herbicide resistance development, and control of late-emerging weeds is important.
Keywords: Resistance management; residual control